(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
This study looked at how using small or large pieces of Rice Husk Ash and Waste Paper Sludge Ash can affect how strong and how much the concrete shrinks when it dries. When Rice Husk Ash (RHA) and Waste Paper Sludge Ash (WPSA) were added to concrete, more water was needed. However, the mechanical properties of the concrete were similar or better than the concrete made with just Ordinary Portland Cement (OPC). Finer RHA and WPSA gave the best improvements. Rice husk and waste paper ash made things shrink a lot because of tiny particles that cause it to happen. This research looked at using waste paper sludge ash instead of some of the cement in a kind of concrete called M20 mix. They tested different amounts of the ash (0%, 5%, 10%, 15%, 20%, and 25%) to see how strong it made the concrete. They tested the strength of the concrete up to 28 days after it was made and compared it to normal concrete. Waste paper sludge can be used as fuel because it has a lot of heat energy. Afterwards, the remaining ash can be used to replace some of the cement.